Kapitalismus in der Misstrauensfalle - Michael Hüther (Wirtschaftsdienst, 2023)
– The war in Ukraine has not only dramatically changed Western perceptions of geopolitics, but also influenced risk assess-ments of economic interdependencies between Western economies and China. China has gradually emerged as an important, and in some cases indispensable, supplier to Western economies. The illusion of a gradual development and spread of Western values in the wake of the globalisation has failed. The paper discusses the challenges that China faces, i.e. the dramatic effects of demography, the misallocation of goods or its own dependencies on the West. The West cannot avoid the systemic conflict if it wants to remain a major global player, but it must clearly state its own interests.
Keywords: F02; F60; 330; Internationale Wirtschaft; Internationale Wirtschaftsbeziehungen; China; Westliche Staaten